Perspectives on global nursing leadership: international experiences from the field. (December 2014) - Buckner, E.B.; Anderson, D.J.; Garzon, N.; Hafsteinsdóttir, T.B.; Lai, C.K.Y.; Roshan, R.
Abstract : Aim: Nursing leaders from six countries engaged in a year‐long discussion on global leadership development. The purpose of these dialogues was to strengthen individual and collective capacity as nursing leaders in a global society. Field experiences in practice and education were shared. Perspectives on global leadership can strengthen nurses' contributions to practice, workplace and policy issues worldwide. Background: Transformational leadership empowers nurses' increasing confidence. Mentoring is needed to stimulate leadership development but this is lacking in many settings where nurses practice, teach and influence policy. Organizations with global mission provide opportunity for nurses' professional growth in leadership through international dialogues. Procedures: Dialogues among participants were held monthly by conference calls or videoconferences. Example stories from each participant illustrated nursing leadership in action. From these exemplars, concepts were chosen to create a framework. Emerging perspectives and leadership themes represented all contexts of practice, education, research and policy. The cultural context of each country was reflected in the examples. Results: Themes emerged that crossed global regions and countries. Themes were creativity, change, collaboration, community, context and courage. Implications for Nursing and Health Policy: Relationships initially formed in professional organizations can be extended to intentionally facilitate global nursing leadership development. Exemplars from the dialogues demonstrated nursing leadership in health policy development within each cultural context. Recommendations are given for infrastructure development in organizations to enhance future collaborations.